Imperialism and Dependency: The Peripheral States under Capital´s Structural Crisis and the Necessity for an Anti-imperialist Alliance - Ferreira, Carla (APISA, 2021)
The destructiveness that increasingly characterizes social and economic relations these days has made the debate over the necessity for building a counter-hegemonic power against imperialism an urgent issue. Regarding this debate, the contribution of the Hungarian philosopher István Mészáros seems extremely relevant to us. Mészáros describes the logic of capital reproduction in this present phase and verifies the trend for destructive consumption as its pattern (Mészáros, 2002: 678)...